2016
DOI: 10.1159/000448924
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery in Recurrent Glioblastoma

Abstract: Background: We evaluated Gamma Knife radiosurgery (GKRS) as a treatment option for patients with recurrent glioblastoma. Patients and Methods: 42 patients with histopathologically diagnosed recurrent grade IV tumor were treated with GKRS. All patients had undergone standard multimodal first-line treatment. The average time from diagnosis to GKRS was 17.0 months. The median target volume was 5.1 cm3. The median margin dose was 10 Gy and the median central dose 20 Gy. In a subset of patients, O6<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…Although this was a non-randomized study, favorable prognostic factors included smaller tumor volume, younger age, high KPS and lower grade (47). Several other studies found age and performance status to be significantly associated with survival (40,41,45). Two other retrospective reports showed that higher KPS and small tumor volume predicted for increased OS (48).…”
Section: Prognostic Indicatorsmentioning
confidence: 75%
See 1 more Smart Citation
“…Although this was a non-randomized study, favorable prognostic factors included smaller tumor volume, younger age, high KPS and lower grade (47). Several other studies found age and performance status to be significantly associated with survival (40,41,45). Two other retrospective reports showed that higher KPS and small tumor volume predicted for increased OS (48).…”
Section: Prognostic Indicatorsmentioning
confidence: 75%
“…One study showed a significant median OS benefit in patients with MGMT promoter methylation (33.4 vs. 16 months). However, only 22 patients had MGMT sequencing at the time of this study (41). Another report had 11 patients with MGMT promoter methylation, but did not find a statistically significant difference between OS in the cohort (40).…”
Section: Prognostic Indicatorsmentioning
confidence: 76%
“…The current practice is to re-evaluate all treatment modalities used in first line for the individual benefit when used in the particular recurrence. In small recurrent GBM, radiosurgery presents a valuable alternative to surgical resection [49].…”
Section: Treatment After Progressionmentioning
confidence: 99%
“…Most of the recurrences are observed within the initial tumor bed or irradiated volume [4,5]. The median overall survival (OS) for patients with recurrent GBM reported in the literature ranges between 5.3 and 24 months [6][7][8][9][10][11][12]. There is no standard salvage treatment after recurrence.…”
Section: Introductionmentioning
confidence: 99%